Multimedia Instructional Unit for the Approach of Statistical Topics in the High School Diploma for Adults Program Using the eXeLearning Technological Tool - Navarro, Carlos (2019)
In Costa Rica, before 2016 the subject of statistics was not included in the national high school tests in Mathematics. As of 2016, the test, consisting of 60 items, includes 9 statistical items. On the other hand, teachers in their lessons usually use traditional expository methods, mediated by the use of a blackboard and printed materials. In this context, a need to create and implement new teaching techniques in this area was evident, for which a Multimedia Instructional Unit in Statistics was developed and applied through the eXeLearning technological tool. The instructional unit was applied to a group of 30 students belonging to the high school diploma for adults program from the region of Turrialba in Costa Rica. We used a qualitative, interpretive and naturalistic method based on the generation of analysis categories. It was determined that a simple way to show the information and the inclusion of review activities, exemplification, practice and evaluation activities, is desired and well valued by the students. In addition, it was observed that the technological means promoted student interest and motivation, while facilitating the monitoring of the proposed activities and the automatic generation of progress and evaluation reports. It was concluded that the Multimedia Instructional Unit is a didactic complement to the work of the teacher of mathematics, especially in distance education since it allowed self-taught management of the student and achieved their attention and motivation.